Radiation Application in Consumers’ and Health Applications - A Preliminary Review - Mohd Shamsuri, Siti Balqis; Othman, Siti Amira; Jasrin, Nurun Saqinah (Semarak Current Biomedical Technology Research Journal, 2024)
Irradiation method has received a tremendous attention in recent years especially as a consumer and health application. For consumer product, any compound that can be used as a cleaning agent is known as a detergent. Detergents are known with their natural radioactivity levels like other industrial products. While in the health application, generally people in many regions of the world still do not get enough iodine and iodine deficiency remains a public health issue. Around 30 % of the world's population is at danger of iodine deficiency. According to Oxford Advances Learning Dictionary, the word adsorb is defined as the accumulation of liquid or gas on surface of a substance. Meanwhile, thyroid is gland in the neck that produces hormone which regulate and control the body growth and function. Thus, from this review, the topic is basically about the effects when iodine is adsorbed in the thyroid gland that could cause thyroid disease. Review on the irradiated detergent is also presented.